2022
DOI: 10.1186/s12905-022-01622-3
|View full text |Cite
|
Sign up to set email alerts
|

The unspoken grief of multiple stillbirths in rural Pakistan: an interpretative phenomenological study

Abstract: Background Pakistan has the highest rate of stillbirth (30.6 stillbirths per 1000 total births) as compared to other South Asian countries. The psychological impact of stillbirths on bereaved women is well documented; however, there is a dearth of literature on lived experiences of women with multiple stillbirths in Pakistan. Objective The purpose of this research is to understand the lived experiences of women who had multiple stillbirths in Thatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…We have previously conducted studies on women’s experiences of childbirth in health facilities and reported our findings. 20 , 36 , 73 Second, the sensitive nature of the topic may have introduced a bias of social desirability whereby providers might have felt reluctant to speak, resulting in the under-reporting of disrespectful and abusive behaviors prevalent at the health facility. Third, study participants were selected from secondary-level health facilities in 2 districts of Sindh.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously conducted studies on women’s experiences of childbirth in health facilities and reported our findings. 20 , 36 , 73 Second, the sensitive nature of the topic may have introduced a bias of social desirability whereby providers might have felt reluctant to speak, resulting in the under-reporting of disrespectful and abusive behaviors prevalent at the health facility. Third, study participants were selected from secondary-level health facilities in 2 districts of Sindh.…”
Section: Discussionmentioning
confidence: 99%
“…Stillbirths decreased among highly educated women over the entire study period compared to uneducated women due to the change in characteristics, but a surprising result from the behavioral changes showed that highly educated women contributed more to the change in stillbirth rates from 2012 to 2017. This surprising result of a higher uptake of stillbirth among highly educated women might be because uneducated mothers may underreport stillbirths due to social stigmas and taboos (16). However, other studies found that the risk of stillbirth was less likely to occur among educated mothers (37-39).…”
Section: Issues a Ecting Womenmentioning
confidence: 93%
“…Underreporting these issues due to social taboos is one of the reasons for this unrecognized health problem (13). Pakistani women are reluctant to discuss stillbirths for fear of being stigmatized as infertile or being subject to misconceptions such as the influence of an evil eye or black magic (16). Globally, stillbirths were not a priority within the Millennium Development Goals (MDGs).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers used the concept of bracketing during the analysis of the data. All the preconceived ideas, personal observations, and reflexive notes were written by the authors before the data analysis [ 32 ]. The inductive method was used to identify significant themes [ 33 ].…”
Section: Methodsmentioning
confidence: 99%